Retinoic Acid Induces Embryonic Stem Cells (ESCs) Transition to 2 Cell-Like State Through a Coordinated Expression of Dux and Duxbl1 - Tagliaferri, Daniela; Mazzone, Pellegrino; Noviello, Teresa M. R.; Addeo, Martina; Angrisano, Tiziana; Del Vecchio, Luigi; Visconte, Feliciano; Ruggieri, Vitalba; Russi, Sabino; Caivano, Antonella; Cantone, Irene; De Felice, Mario; et al. (Frontiers in Cell and Developmental Biology, 2020)
Embryonic stem cells (ESCs) are derived from inner cell mass (ICM) of blastocyst. In serum/LIF culture condition, they show variable expression of pluripotency genes that mark cell fluctuation between pluripotency and differentiation metastate. The ESCs subpopulation marked by zygotic genome activation gene (ZGA) signature, including Zscan4, retains a wider differentiation potency than epiblast-derived ESCs. We have recently shown that retinoic acid (RA) significantly enhances Zscan4 cell population. However, it remains unexplored how RA initiates the ESCs to 2-cell like reprogramming. Here we found that RA is decisive for ESCs to 2C-like cell transition, and reconstructed the gene network surrounding Zscan4. We revealed that RA regulates 2C-like population co-activating Dux and Duxbl1. We provided novel evidences that RA dependent ESCs to 2C-like cell transition is regulated by Dux, and antagonized by Duxbl1. Our suggested mechanism could shed light on the role of RA on ESC reprogramming.